THE INFLUENCE OF ANIME ON JAPANESE LITERATURE STUDENTS AT BUNG HATTA UNIVERSITY - Sisi ayusafitri; Irma; Diana Kartika; Dewi Kania Izmayanti (Hikari: Jurnal Bahasa dan Kebudayaan, 2023)
This research aims to determine the influence of anime on the cultural knowledge and language proficiency of Japanese Literature students at Bung Hatta University. The research method used is descriptive qualitative with data collection techniques in the form of questionnaires and interviews. The results of the study indicate that watching anime can have a positive influence on students, especially in terms of knowledge and understanding of Japanese customs, traditions, religion, values, and norms that are part of Japanese culture, as well as improving Japanese language proficiency such as vocabulary, conversation, and listening skills.